Readmission and mortality in patients treated by interprofessional student teams at a training ward compared with patients receiving usual care: a retrospective cohort study - Hallin, Karin (BMJ Open, 2018)
OBJECTIVE: This study aimed to compare the rate of patient readmissions and mortality between care provided at an orthopaedic interprofessional training ward (IPTW) and usual care. DESIGN: Retrospective cohort study. SETTING: Orthopaedic wards at a level II trauma centre at a Swedish university teaching hospital between 2006 and 2011. PARTICIPANTS: Two cohorts were identified: (1) a control cohort that had not received care at the IPTW, and (2) patients who had been treated for at least 1 day at the IPTW. MAIN OUTCOME MEASURES: Readmission at 90 days and 1-year mortality. RESULTS: We included 4652 controls and 1109 in the IPTW group. The mean age was 63 years, and 58% were women. The groups did not differ in any of the outcomes: the readmission rate in the control and IPTW groups was 13.5% and 14.0%, respectively, while mortality was 5.2% and 5.3%, respectively. This lack of difference remained after adjusting for confounders. CONCLUSION: Interprofessional undergraduate training in patient-based settings can be performed in a level II trauma hospital with satisfactory patient safety.